2021
DOI: 10.1111/and.14345
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of platelet indices and mean platelet volume to platelet count ratio in experimentally varicocele‐induced adolescent and adult rats

Abstract: The present study investigated the sperm quality parameters and platelet indices in adolescent and adult varicocele rats. Twenty male Wistar rats were distributed into four groups (n = 5): I—sham adolescent group, II—sham adult group, III—varicocele adolescent group, and IV—varicocele adult group. Rats were sacrificed on the 61st day of the experiment. Sperm count (×106 ml−1), sperm motility and viability (%) were significantly (p < 0.05) different between varicocele and sham groups in adolescent and adult rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Compared with the nondiabetic control rats, the female diabetic rats of the 7‐day diabetic group in this study showed a moderate increase in MPV to PLT, but not as marked as the 28‐day diabetic female rats. Several studies have shown that a low PLT may suggest increased platelet activation in humans with cardiovascular disease by increasing glycoprotein VI and inflammatory marker levels 26–28 . The MPV‐to‐PLT ratio, along with other platelet indices, were used for the first time in diabetic male and female rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the nondiabetic control rats, the female diabetic rats of the 7‐day diabetic group in this study showed a moderate increase in MPV to PLT, but not as marked as the 28‐day diabetic female rats. Several studies have shown that a low PLT may suggest increased platelet activation in humans with cardiovascular disease by increasing glycoprotein VI and inflammatory marker levels 26–28 . The MPV‐to‐PLT ratio, along with other platelet indices, were used for the first time in diabetic male and female rats.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that a low PLT may suggest increased platelet activation in humans with cardiovascular disease by increasing glycoprotein VI and inflammatory marker levels. [26][27][28] The MPV-to-PLT ratio, along with other platelet indices, were used for the first time in diabetic male and female rats. The correlation observed in this study between MPV and the MPV-to-PLT ratio with glucose was positively strong and moderate in female and male rats, respectively.…”
Section: F I G U R Ementioning
confidence: 99%